Efektivitas Pelaksanaan Undang-Undang Nomor 28 Tahun 2014 tentang Hak Cipta Di Bidang Fotografi Di kota Palopo - Salmi (Madani Legal Review, 2020)
The problem in this paper is how the legal protection of copyright law in the field of photography in the city of Palopo and what factors are obstacles to the implementation of copyright law in the field of photography in the city of Palopo. The research method in this paper is empirical normative. The results of the research in this paper are: First, the implementation of copyright protection arises automatically based on declarative principles after a work is realized in real form without reducing restrictions in accordance with statutory provisions. Based on Law Number 28 of 2014 concerning Copyright on Portraits can be done in 2 (two) ways, namely by preventing the registration of Copyright with the Directorate General of Intellectual Property Rights, and being repressive, namely filing a lawsuit to the Commercial Court if a violation of the Rights Copyright for Portraits. Second, the factors which hinder the implementation of the Copyright Act in Palopo City are economic, educational factors, and the lack of law enforcement in following up perpetrators of violations of photographic works because some photographers do not list their aspirations, so that perpetrators of violations never feel reddened for their actions